OS PEQUENOS BOTÕES E O DESESPERADO DESABROCHAR DE UMA JOVEM POESIA... - Carmen Lucia Tindo (TRF2, 2018)
Carla Queiroz is a young representative of Angolan poetry post-1990. His writing focuses on not only a poetic eroticism restricted to females. She seeks the Eroticism of the word, the metalanguage and reflections on the Angolan society, whose disenchantment must be overcome. In this sense, it offers the honey of your poetry as a form of resistance to the dystopia social context.